Waqf Management in Pesantren: A Case Study of Lembaga Wakaf Daarut Tauhiid - Dharmarianti, Dian Putri; Hasanah, Neneng; Irfany, Mohammad Iqbal; Haq, Daffa Aqomal (SMART Insight, 2024)
Waqf, as an instrument for wealth distribution in Islam, must have an impact on people's well-being. However, in actuality, waqf collection and management in Indonesia is substandard. As a result, as a nazir, the Lembaga Wakaf Daarut Tauhiid Institution must be able to collect and administer waqf assets properly. The purpose of this research is to analyze the waqf institutions' strengths, weaknesses, opportunities, and dangers, as well as to develop strategies for collecting and managing waqf assets in the Wakaf Daarut Tauhiid Institution. In this study, the Analytic Network Process (ANP) with a SWOT structure system was applied. The most influential feature of strenth was discovered to be the presence of figure. The most serious shortcoming is a lack of education and outreach to prospective waqf. The most crucial feature of the possibility is the high potential of waqf. The most potent part of threat is waqf faith in waqf organizations. The approach for effective waqf asset management prioritizes the promotion of waqf initiatives using social media. The created plan is designed to serve as a guide for stakeholders in creating future policies.